Pengaruh Leverage, Kepemilikan Institusional, Dan Profitabilitas Terhadap Tax Avoidance Pada Perusahaan Jasa Yang Terdaftar Di Bei Pada Periode 2019 – 2022 - Arief Kurniawan; Nurfauziah Nurfauziah (Jurnal Riset Akuntansi, 2023)
This researach aims to understand the effect of leverage, institutional ownership, and profitability on tax avoidance. The author uses quantitative data in the form of company financial statements. The author collected data using the purposive sampling method for service companies listed on the Indonesian Stock Exchange in the 2019 – 2022 period and processed using the Eviews 12 statistical application. There was a total of 42 entities and 168 samples were collected. This study shows the results that leverage has a positive impact on tax avoidance, then the results of institutional ownership have a positive impact on tax avoidance, and finally, profitability has a negative relationship to tax avoidance.